PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN PRODUKTIVITAS KERJA GURU DI MADRASAH DAN TPA ALI ADAM COPER PONOROGO - Astuti, Johan Wahyu Tri; Sa’adah, Fibrian Miftahus (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
The head master is a leader in an Islamic educational institution who has a very important role in growing teacher work productivity, because if teacher productivity is not paid attention to, it will have an impact on decreasing the quality of teaching and a lack of innovation in learning. So this research aims to determine the role of head master in increasing teacher work productivity in TPA Ali Adam Coper Ponorogo. This research uses a qualitative case study type approach, for main data collection using in-depth interviews through semi-structured interview guidelines with heads and teachers TPA Ali Adam Coper, the data analysis model used is Miles and Huberman which goes through three stages, namely data condensation, data presentation and conclusion drawing. The results of this research found that, the role of the head master in increasing teacher work productivity through the leadership model of momong, among, and ngemong, so that teachers at the TPA Ali Adam are motivated to take part in various activities and training both inside and outside the madrasa that can support productivity teacher work. This is a valuable investment for teachers' professional development, which aims to improve the quality of the education they provide, thereby increasing student and parent satisfaction.